The Effect of Medial Sural Artery Perforator Flap on Reconstruction of Soft Tissue Defects: A Meta-Analysis With Multiple Free Soft Flaps. Issue 5 (July 2021) - Xu, Qiang; Yin, Shou-Cheng; Su, Xing-Zhou; Wang, Si-Min; Liu, Yi-Hao; Xu, Zhong-Fei
Abstract : Background: With the gradual popularity of relatively novel medial sural artery perforator flap (MSAPF), robust studies are needed to compare the surgical outcomes of MSAPF versus multiple free soft flaps (MFSFs) to verify the advantages and disadvantages of MSAPF. Methods: The authors searched PubMed, Web of Science, EMBASE, Cochrane Library, Chinese BioMedical Literature Database (CBM), and China National Knowledge Infrastructure (CNKI) until September, 2020, to identify studies that compared surgical outcomes of MSAPF and MFSFs. Two authors followed the PRISMA guidelines, individually extracted the data and performed the quality assessments. Survival rate of flaps, satisfaction degree of patients in recipient and donor site, skin grafting, and morbidity of recipient and donor site were evaluated. Results: A total of 441 cases from 7 studies were included in our analysis. No significant differences were found regarding survival rate of flaps, recipient morbidity, and recipient satisfaction degree between the 2 groups. However, MSAPF group was significantly superior to MFSFs group in terms of skin grafting, morbidity, and satisfaction degree of donor site. Conclusion: Our meta-analysis showed that the MSPAF and MFSFs groups were similar in terms of survival rate of flaps, recipient morbidity, and recipient satisfaction degree. Medial sural artery perforator flap group was superior to MFSFs group in terms of morbidity and satisfaction degree of donor site. The results may prove that MSAPF is gaining popularity for a reason and is a good choice for repairing soft tissue defects. Abstract : Supplemental Digital Content is available in the text